Evaluation Of Knowledge, Attitude And Beliefs Regarding Medicines Among Primary Schoolchildren - Dawood, Omar Thanoon (2010)

(untitled)
The use of medicine for the treatment of health problems is a common practice among children. Most children are forming attitudes, beliefs and expectations about medicines through their past experience with medicines, through the parents or by observing family members taking medicines. Very few studies have been conducted about medicine knowledge among Malaysian children. This study aimed to evaluate knowledge, attitudes and beliefs about medicines among primary schoolchildren and identify those factors that may associate with their knowledge, attitudes and beliefs. A cross-sectional survey was conducted among schoolchildren from grades 5 and 6 in four primary schools in Penang Island. A convenience and purposive sampling methods were used to collect the data through a self-administered questionnaire to all schoolchildren and their parents.